DA'WAH ULAMA IN INSTILLING THE VALUE OF TAWASSUTH AND RELIGIOUS MODERATION: A STUDY OF THE PERSPECTIVES OF THE QUR'AN AND HADITH IN THE ERA OF SOCIETY - Risqiatul Hasanah; Ali Muammar; Mahyuddin Barni (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
The principle of tawasuth or moderation in the Qur'an is one of the important teachings that directs Muslims to live a balanced life. Moderation is not only related to worship, but also includes property management, social behavior, and attitudes in religion. This study aims to examine the concept of tawasuth based on the interpretation of Tafsir Al-Misbah by Quraish Shihab on several verses that support this principle, namely Surah Al-Baqarah (2:143), Al-Furqan (25:67), and Luqman (31:19). Through a qualitative analysis approach, this study shows that tafsir Al-Misbah promotes the principle of moderation in practicing religion in a harmonious manner and is relevant for daily life. The conclusion of this study reveals that moderation is a key value that can prevent extremism and build a balanced and just society.